Comparison of trunk alignment and postural habits of high school adolescents and university students - Jankowicz-Szymańska, Agnieszka; Wódka, Katarzyna; Kawa, Justyna; Kwiek, Bernadetta (Health Promotion & Physical Activity, 2022)
Introduction: It is widely believed that the postural quality of adolescents is poor and this condition is blamed, at least in part, on a sedentary lifestyle and low self-awareness of body alignment and awareness of movement quality. The aim of this study was to evaluate the postural habits and trunk alignment of high school adolescents against university students with high physical activity and high awareness of the importance of postural quality for health. Material and methods: 59 high school students and 82 university students, male and female, participated in the study. Three-dimensional trunk positioning in habitual standing was investigated using the Zebris Pointer ultrasound device. Awareness of habitual posture during various activities of daily living was assessed using a validated questionnaire. Results were analysed using Statistica v13. Results: High school students were characterised by a greater depth of thoracic kyphosis than university students. Female high school students tended to have shallower lumbar lordosis and male high school students tended to have deeper lordosis. High school students showed worse lateral trunk inclination and greater pelvic to shoulder rotation. The most important observation regarding postural awareness was related to sitting position. Women from both groups were more likely than men to admit to sitting with a bent and rotated trunk and crossed legs. Conclusions: It appears that higher physical activity and / or greater knowledge of university students contributes to more correct trunk positioning compared to the physically inactive high school students. Postural habits, however, are similar in both groups. Gender significantly differentiates both posture and posture-related habits.